Kinerja Robot Self Balancing pada Lintasan Bergelombang Menggunakan Pengendali PID Digital - Cendana, Bayu; -, Sugeng; Sikki, Muhammad Ilyas (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2020)
A two-wheeled self-balancing robot is a mobile robot with two wheels on each side. It is equipped with a controller which balances it. A PID controller can be used to control robot’s position so that it can move steadily in bumpy surfaces. Its PID controller moves by calculating suitable proportional constant (Kp), constant integral (Ki) and derivative constant (Kd) using trial and error method. The analysis of controlling system is based on three aspects of analysis; transient response analysis, steady state response analysis, and stability analysis. The results of present research show that the robot maintained its balance when it moved on a bumpy surface with Kp of 50, Ki of 170 and Kd of 2,2. The analysis of PID parameter suggests that the response of self balancing robot is categorized as overdamped with the percentage of error steady state of1,02% while its stability is categorized as marginally stable.